Pengaruh Jenis dan Konsentrasi Anti-Browning Agent Terhadap Mutu Fisik Tepung Jewawut (Foxtail Millet) - Islamiyah, Syahmidarni Al; Samang, Andi Marlisa Bossa; Nurhafnita, Nurhafnita (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
The purpose of this research was to determine the effect of the type and concentration of anti-browning agents (sodium metabisulfit and citric acid) on the physical quality of millet flour, especially the degree of whitness and calor (lightness, redness, yellowness) and determine the best treatment. This study used experimental method. The reseach design used was a Completely Randomized Factorial Design (RALF) with two factors, namely faktor A was the type of anti-browning agent consisting two levels (sodium metabisulfite and citric acid), faktor B was concentration of the anti-browning agent consisting three levels (1,5%, 2%, 2,5%). Fromthe two factors, six treatments were obtained, and each treatment was repeated three times. Data were statistically analyzed using analysis of variance (ANOVA) and then continued with Duncan`s New Multiple Range Test (DNMRT) at 5% level. Results of the research showed that the type of anti-browning agent significantly affected the degree of whiteness, lightness, redness, and yellownes of millet flour. Concentrasion has a significant effect on the lightness value and redness value, but doesnt have a significat effect on the degree of whitness and yellowness value. The interaction of the two factors (type and concentration) has a significant effect on the lightness value, redness value, and yellowness value, but has no significant effect on the degree of whitness. Based on the physical quality of millet flour produced in this study, namely the degree of whiteness, lightness, redness, and yellowness, the best treatment is sodium metabisulfite soaking.